2022
DOI: 10.1128/spectrum.00381-22
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Development of Colistin Resistance during Colistin Treatment of Carbapenem-Resistant Klebsiella pneumoniae Infections

Abstract: Treatment of carbapenem-resistant Klebsiella pneumoniae (CRKP) infections is challenging due to the limited options of antibiotics. Colistin is one of the last-resort antibiotics if novel antimicrobial agents are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Как правило, у K. pneumoniae колистин-резистентность ассоциируется с карбапенем-резистентностью. В нашем исследовании все штаммы CRKP продуцировали карбапенемазы, как и в исследовании P. Huang et al (2022); в некоторых работах продукция карбапенемаз у CRKP была ниже -73-77% [14,19,27]. Нами выявлено преобладание 2 типов карбапенемаз у CRKP -OXA-48 и NDM.…”
Section: Discussionunclassified
“…Как правило, у K. pneumoniae колистин-резистентность ассоциируется с карбапенем-резистентностью. В нашем исследовании все штаммы CRKP продуцировали карбапенемазы, как и в исследовании P. Huang et al (2022); в некоторых работах продукция карбапенемаз у CRKP была ниже -73-77% [14,19,27]. Нами выявлено преобладание 2 типов карбапенемаз у CRKP -OXA-48 и NDM.…”
Section: Discussionunclassified
“…We found no link between colistin-resistant isolates and previous exposure to colistin [ 21 , 22 , 27 , 28 , 32 ]. However, the findings on this topic are still controversial [ 31 , 33 ]; one study found a protective effect for the use of colistin–tigecycline combination therapy [ 34 ], whereas another showed a protective effect for aminoglycosides in acquired colistin-resistant strains [ 23 ]. In our institutions, colistin is used when a CPE infection is suspected and confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline susceptibility was based on the US Food and Drug Administration criteria (susceptible, MIC≤2 mg/L; resistant, MIC≥8 mg/L). 12 Escherichia coli ATCC25922 and Pseudomonas aeruginosa ATCC27853 were used as quality control standards.…”
Section: Methodsmentioning
confidence: 99%